LITHOLOGICAL STRUCTURE AND FACIES FEATURES OF THE KERLEUTIAN SEDIMENTS OF THE BLACK SEA MEGADEPRESSION - HNIDETS, Volodymyr; HRYHORCHUK, Kostiantyn; REVER, Anastasiia; KOKHAN, Oksana (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. As part of the Maikop sedimentary complex of the Black Sea megadepression, the Middle Maikop deposits are the most interesting in economic aspect, which is proven by the discovery of a number of oil and gas fields. The Middle Maikop deposits in the lower and upper subhorizons of the Kerleut regiostorey usually conformably lie on the Lower Maikop deposits, and are overlapped without a visible break by the Upper Maikop deposits. The completeness of their section is characterized by significant spatial variations. The maximum thicknesses (over 2000 m) are observed on the territory of the Kerch Peninsula and in the southeastern regions of the Plain Crimea (1800 and more meters). Instead, in the north of the Plain Crimea in the Syvash and Northern Black Sea, shortened sections have been discovered, the thickness of which ranges from 200–300 m to 400–500 m. Within the water area of the northwestern shelf of the Black Sea, it does not exceed 650 m. In tectonic terms, the Black Sea megadepression consists of several coulisse-like articulated negative structural elements of a higher order: the Karkinit-North Crimean, Indolo-Kuban and South Kerch depressions. The aim of the work is to establish the features of the lithological and lithmological structure of the Middle Maikop (Kerleut) stratum of the Black Sea megadepression, to study the structural-textural and mineralogical-petrographic features of the rocks in the context of reconstructing the conditions of their sedimentation.Methods. Lithological dismembering of well sections was carried out by interpreting the results of well logs (radioactive methods). The features of the development of sedimentary bodies of different composition were clarified on the basis of the segregate of lithmites according to the method (Karogodyn, 1980). This approach was tested in the study of the Maikop layers of the North Crimean and Indolo-Kuban depressions (Gnidets et al., 2023). The work used the breakdowns developed and adopted for use by geologists of the KP "Pivdenyekogeocenter". Petrographic studies (over 400 thin sections, collection of the Department of Sedimentology of Fuel Provinces of the Institute of Geology and Geochemistry of the National Academy of Sciences of Ukraine) were performed by the authors under a Carl Zeiss Jena polarizing microscope.Resuls. The spatial-age features of the lithological-lithmological structure of the Kerleut strata of the Black Sea megadepression have been clarified. Four lithological complexes have been identified: sandy-silty (clastic rocks over 60%); silty (50–60%); argillaceous-silty (40–60%) and argillaceous (less than 40 %), which are characterized by the regularity of replacement from the marginal parts to the depocenters of depressions. Sections of the middle Maikop stratum are composed of 20–84 lithmites of regional, zonal and local distribution, 20–200 m thick, silty (23%), mixed (22%) and clayey (55%) fields. Several levels of development of different-rank silty-sandy units (K1–K2–K3–K4) have been identified, and the features of their spatial distribution have been established. The specificity of the lithological structure of the sediments of the Black Sea-Crimean (thickness of lithology bodies up to 100 m) and Azov-Black Sea (thickness of lithology bodies no more than 40 m) sedimentary-rock basins has been revealed.Conclusions. The established features of the spatial-age variability of the lithological-lithmological structure of the Middle Maikop stratum will serve as the basis for creating a model of the conditions of their sedimentation within the Crimean segment of the eastern Paratethys, will contribute to understanding the nature of the spatial-age distribution of reservoir rocks and seals, and will determine the main directions of geological exploration work in the region.
Keywords: Paratethys; Black Sea megadepression; Middle Maikop; Kerleutian horizon; lithogenesis